The geographic distribution of retail tobacco outlets in Yogyakarta, Indonesia. (28th March 2021) - Morrison, Christopher N.; Lee, Juliet P.; Giovenco, Daniel P.; West, Brooke; Hidayana, Irma; Astuti, Putu A. S.; Mooney, Stephen J.; Jacobowitz, Ahuva; Rundle, Andrew
Abstract: Introduction: Tobacco smoking prevalence in Indonesia is among the highest in the world. Research worldwide identifies that physical access to tobacco through retail outlets is related to increased tobacco smoking. Tobacco outlet density is very high in many Indonesian cities, so tobacco access may contribute to the high prevalence of tobacco use in that country. The aim of this study was to examine distributions of tobacco outlets in one Indonesian city, Yogyakarta, in relation to social and physical environmental conditions. Methods: For this cross‐sectional ecological study, we virtually audited randomly selected street segments (n = 1099) using Google Street View. The outcome of interest was a count of tobacco advertising banners (indicating the presence of retail outlets). Exposures were physical environmental conditions (scales of main roads, physical decay, presence of schools, mosques, churches) and social conditions measured at the neighbourhood level (concentrated disadvantage, age composition, population density). Results: Tobacco banners were present on 36.4% of sampled street segments, including 55 (37%) of 147 streets with schools; a total of 1381 banners were identified. Multilevel negative binomial regression models for street segments nested within neighbourhoods found the prevalence of tobacco banners per 100 m was lower near schools (RR = 0.66, 95% CI 0.45, 0.97) and was not associated with other exposure measures. Discussion and Conclusions: Retail tobacco outlets are ubiquitous in Yogyakarta. Although they are relatively less prevalent on streets with schools, the high absolute values and wide spatial distribution means all residents of Yogyakarta are exposed to tobacco outlets.